Legal frameworks and practical challenges: a review of the enduring failure to prevent family separations in armed conflicts - Boothby, Neil (Frontiers in Psychology, 2025)
The separation of families during armed conflicts remains a persistent tragedy, inflicting suffering on individuals and tearing apart the social fabric of communities. Despite the existence of international laws and conventions designed to protect families and ensure their reunification, the international community continues to fall short in preventing these separations. This review seeks to analyze the multifaceted reasons behind this ongoing challenge by examining the relevant international legal frameworks and the limitations and practical challenges faced by local, national, and international actors. It further seeks to explore the underlying causes of separation, and unintended consequences of humanitarian responses, drawing on lessons learned from past and present conflicts, in an effort to illuminate potential pathways to more effective actions.